Sistem Pakar Diagnosa Penyakit THT Menggunakan Metode Backward Chaining - Mardi Turnip (RJOCS (Riau Journal of Computer Science), 2015)
Disease THT (Telinga, Hidung dan Tenggorokan) is a public health problem, because it often occurs without knowing the season. This disease can affect various ages. This expert system development process is done using backward chaining inference engine where the search process starts from the facts to further toward a conclusion. In addition serves to lighten the work of doctors, expert systems developed will also be very beneficial to the general public in accessing information about THT diseases such as diagnosis and therapy. With this application will help users and THT physicians in performingservice and access to information related to the diagnosis of THT diseases